2021
DOI: 10.2196/30325
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and Game-Based Strategies for Dermatology Education: Narrative Review

Abstract: Background Game-based approaches, or gamification, are popular learning strategies in medical education for health care providers and patients alike. Gamification has taken the form of serious educational games and simulations to enable learners to rehearse skills and knowledge in a safe environment. Dermatology learners in particular may benefit from gamification methods, given the visual and procedural nature of the field. Objective This narrative rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
(41 reference statements)
0
10
0
1
Order By: Relevance
“…The gamification principles of meaningful purpose, meaningful choice, supporting player archetypes, feedback, and visibility proposed by Floryan et al [ 66 ] could enhance the user experience and engagement within digital health interventions. Gamification could increase motivation, reinforce learning objectives, and increase enjoyment and positive experiences in dermatological education and prevention approaches [ 9 ]. Likewise, programmed reminders are an effective way to promote prevention habits, highlighted by the use of text messages in dermatology [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gamification principles of meaningful purpose, meaningful choice, supporting player archetypes, feedback, and visibility proposed by Floryan et al [ 66 ] could enhance the user experience and engagement within digital health interventions. Gamification could increase motivation, reinforce learning objectives, and increase enjoyment and positive experiences in dermatological education and prevention approaches [ 9 ]. Likewise, programmed reminders are an effective way to promote prevention habits, highlighted by the use of text messages in dermatology [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The former can be defined as interventions provided through a digital environment such as web-based interventions, smartphone apps, SMS text messaging, web-based videos, or wearable devices [ 7 ]. Digital approaches to the prevention of skin cancer present additional advantages such as feedback, interactivity, accessibility, and gamification, which make them suitable and attractive for stakeholders [ 8 , 9 ]. Conversely, possible drawbacks of digital strategies in dermatology could be their availability, financial aspects, reliability, security, confidentially, and lack of education and training of the user [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies will also be identified by hand searching the reference lists of previous systematic reviews related to web-based instruction in HPE [38,44,[49][50][51][52][53][54][55][56][57][58].…”
Section: Hand Searchingmentioning
confidence: 99%
“…Although previous reviews have focused on motivational design features of web-based instruction in HPE [38,44,[49][50][51][52][53][54][55][56][57][58], none have sought to (1) achieve the specific goal of using existing evidence to refine models of motivational design, (2) propose which types of evidence will be required to meet this goal, (3) identify the study designs that can generate such evidence (eg, studies comparing motivational design strategies), and (4) appraise the degree to which studies have generated such evidence. Thus, the value of our review lies in its ability to appraise where we have been and to inform where we ought to go.…”
Section: Overviewmentioning
confidence: 99%
“…In dermatology, game-based interventions promoted learner motivation, enjoyment, and favorable performances (Szeto et al, 2021). Jia et al (2020) demonstrated the effectiveness of the gamified intervention in order to educate young participants on the visual identification of melanoma.…”
Section: Introductionmentioning
confidence: 97%